IMPLEMENTASI TEKNOLOGI DIGITAL DALAM PERKULIAHAN MATAKULIAH KALKULUS INTEGRAL DALAM PENYELESAIAN LUAS DAERAH ANTARKURVA - Meldi, Nadya Febriani; Khoriyani, Rohmah Pila; Susanti, Widya; Ahmad, Dian; Rif'at, Mohamad (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2022)
In today's digital era, the use of digital technology is essential in learning mathematics to create exploratory learning spaces. From an early age, technology in learning needs to be known that it does not only produce manual calculators, but that extensive learning support is realized from various applications or websites used in learning at school or in lectures. However, the lack of knowledge of prospective teacher students is a limiting space for learning space. First, in the integral calculus course, students seem monotonous by only using pencil and paper in learning. This article aims to present the implementation of the use of digital technology in integral calculus lectures in determining the area between curves. The method used is descriptive to describe the implementation of the technology. This was obtained in the implementation of the website using geogebra and wolframalpha as an exploratory tool to create a comprehensive learning space in answering their needs regarding the difficulty of drawing graphs, the difficulty of determining intervals of curve areas, and integral calculations assisted by geogebra and wolframalpha. However, in its use, it is necessary to have a basic understanding of calculating the area between the curves as the main basis for the direction of implementing digital technology.